METHODOLOGICAL PRINCIPLES OF THE INTEGRATED COMPETENCE FORMATION OF FUTURE PSYCHOLOGIST IN THE PROCESS OF TRAINING IN HTEI - Лузік, Е. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The theoretical aspects of application between subject integration are considered. It is discovered as a special purpose result of synergistically mechanism of integral professional area organization in the process of the future practical psychologist study